2002
DOI: 10.1063/1.1531227
|View full text |Cite
|
Sign up to set email alerts
|

Two charge states of dominant acceptor in unintentionally doped GaN: Evidence from photoluminescence study

Abstract: Photoluminescence of the dominant deep-level acceptor in high-purity freestanding GaN is studied over a wide range of excitation intensities. A yellow luminescence ͑YL͒ band at about 2.2 eV saturates with increasing excitation intensity, whereas a green luminescence ͑GL͒ band at about 2.5 eV increases as a square of the excitation intensity. The YL and GL bands are attributed to two charge states of the same defect, presumably a gallium vacancy-oxygen complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
2
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 22 publications
(25 reference statements)
4
85
2
1
Order By: Relevance
“…In photoluminescence (PL) studies of high-quality freestanding GaN grown by HVPE, the yellow luminescence (YL) band with a maximum at about 2.2 eV and the green luminescence (GL) band with a maximum at about 2.4 eV are the dominant defect-related PL bands [5]. Previously, the YL and GL bands were attributed to transitions of electrons from the conduction band to the 2−/− and −/0 transition levels, respectively, of the gallium vacancy-oxygen (V Ga O N ) complex [6]. However, according to recent calculations using hybrid functionals, the PL band caused by transitions of electrons from the conduction band to the 2−/− level of V Ga O N is expected to have a maximum at 1.4 eV; i.e., in the infrared region [7].…”
Section: Introductionmentioning
confidence: 99%
“…In photoluminescence (PL) studies of high-quality freestanding GaN grown by HVPE, the yellow luminescence (YL) band with a maximum at about 2.2 eV and the green luminescence (GL) band with a maximum at about 2.4 eV are the dominant defect-related PL bands [5]. Previously, the YL and GL bands were attributed to transitions of electrons from the conduction band to the 2−/− and −/0 transition levels, respectively, of the gallium vacancy-oxygen (V Ga O N ) complex [6]. However, according to recent calculations using hybrid functionals, the PL band caused by transitions of electrons from the conduction band to the 2−/− level of V Ga O N is expected to have a maximum at 1.4 eV; i.e., in the infrared region [7].…”
Section: Introductionmentioning
confidence: 99%
“…For the samples exhibiting metallic conductivity the presence of acceptors associated with the formation of V Ga Si Ga complexes is also possible. [8] In addition to donor bound excitons and conduction band to acceptor-related features, the photoluminescence spectra contain contributions from donor to acceptors transitions. (for example peak 3 in the 25% Al epilayer).…”
Section: Resultsmentioning
confidence: 99%
“…[4] A significant number of studies have been dedicated to increasing the n-type doping levels in AlGaN [4][5][6] as well as studying the nature of the compensating acceptors [7,8], DX centers [1,3,9], and Si donors [6,7,10] in these alloys through transport and/or PL studies. Optical studies are especially important for highly doped AlGaN epilayers that exhibit a metallic behavior even at room temperature [6,7], such as the ones studied by Hwang et al [6] who reported temperature independent electron concentrations as high as 1.25*10 20 cm -3 in Al 0.5 Ga 0.5 N and 8.5*10 19 cm -3 in Al 0.8 Ga 0.2 N epilayers grown by rf plasma-enhanced molecular beam epitaxy.…”
Section: Introductionmentioning
confidence: 99%
“…The broad YG-PI-L emission band suffers a fast luminescence quenching during irradiation. The YG-PI-L band is likely to be attributed to either the VGaON complex [16], [17] or to the carbon-related defects CN and CNON [17], [18]. The intensity of the B-PL band peaked at 465 nm decreases with fluence increase.…”
Section: Variations Of Characteristics During Proton Irradiationmentioning
confidence: 99%